The Influence of Celebrity Endorsers and Product Knowledge on Purchase Decision for MS. Glow Skincare Product with Brand Image as an Intervening Variable - Siregar, Endang Satriani; Ginting, Paham; Sembiring, Beby Karina Fawzeea (Proceeding of The International Conference on Business and Economics, 2024)
The purpose of this research is to determine the influence of celebrity endorsers and product knowledge on purchase decisions in MS. Glow Skincare Product with brand image as an intervening variable. Researchers collected research data with questionnaires which were distributed to consumers who bought MS. Glow Skincare Products. The research results based on the partial test (t Test) found that: a) there is a significant influence of celebrity endorsers on brand image, b) there is a significant influence of product knowledge on brand image, c) there is no significant influence of celebrity endorsers on purchase decisions, d) there is an influence significant product knowledge on purchase decisions, e) there is no significant influence of brand image on purchase decisions, f) brand image cannot mediate the influence of celebrity endorsers on purchase decisions g) brand image cannot mediate the influence of product knowledge on purchase decisions.